A case study approach to introduce circular economy in sustainable design education (2019)
Finding sustainable solutions to worldwide problems has become a critical challenge for engineers. The use of natural resources and the generation of materials now degradable should be controlled when sustainable solutions are pursued. As a result, the notion of reusing materials and products for longer periods is gaining momentum in the design for sustainability, and the circular economy is becoming the new paradigm to be implemented for that purpose. In contrast to the traditional linear economy that is based on making, using and disposing of products, the circular economy is focused on remanufacturing, reusing and recycling products and materials to extend their life. However, the circular economy is not formally introduced in the academia, and future engineers are not getting prepared to incorporate it into the design for sustainability. This work aims to propose a pedagogical approach to introduce the concept of circular economy in engineering design. A case study is presented to compare the design of a product based on the linear economy model (manufacture, use, waste) and the redesign of the product using the circular economy model (remanufacture, reuse, recycle). The comparison will be attained using sustainability performance indicators considered from early design stages. The contrast between the original design based on the linear economy and the re-design using the circular economy allows illustrating the benefits of the circular economy model to enhance the sustainability performance of a product. © 2019 Institution of Engineering Designers, The Design Society. All rights reserved.